ANALISIS GAYA BAHASA KIASAN DALAM KUMPULAN CERPEN CORAT-CORET DI TOILET KARYA EKA KURNIAWAN - Perawati, Nepa; Martono, Martono; Priyadi, A. Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by the desire of researchers to find the style of figurative language in a collection of short on the Toilet Works by Eka Kurniawan. This study aims to obtain a description of the figurative style style in a collection of short stories on the Toilet Works by Eka Kurniawan. Benefits of research that can be obtained from this research that is, theoretical benefits and practical benefits. The technique used in this research is the technique of documentary study, and the data collection tool is the researcher himself as a key instrument assisted by the recorder card to classify the problem under study. Based on the results of data analysis on a collection of short storieson the Toilet Works by Eka Kurniawan, it can be concluded that there is a figurative style of language consisting of 14 equations of language style, 9 metaphoric style of language, 16 personific languages, and language style of irony 9 pieces, the style of cinema language amounted to 10 pieces, and sarcasm style of 12 units. Based on these conclusions the style of language contained in a collection of short storieson the Toilet Works by Eka Kurniawan all amounted to 70 pieces of the most dominant language style is used is the style of personification language which amounted to 16 pieces.  Keywords: analysis, style, short story